2011
DOI: 10.5039/agraria.v6i3a820
|View full text |Cite
|
Sign up to set email alerts
|

Teores foliares de nutrientes em plantas de camucamuzeiro (Myrciaria dubia (H.B.K.) McVaugh) submetidas a adubações orgânica, mineral e foliar

Abstract: Teores foliares de nutrientes em plantas de camucamuzeiro (Myrciaria dubia (H.B.K.) McVaugh) submetidas a adubações orgânica, mineral e foliar RESUMOO objetivo neste estudo foi avaliar a resposta das plantas de camu-camu (Myrciaria dubia (H.B.K.) McVaugh) por meio dos teores foliares de macro (Ca, Mg, P, K e N) e micronutrientes (Fe, Mn e Zn), em um experimento conduzido na Comunidade do Brasileirinho, localizada na periferia do município de Manaus-AM. O delineamento utilizado foi em blocos casualizados, em es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
1
8
2
1
Order By: Relevance
“…The leaf contents of Mn, cited in this study are higher than those reported by Esashika et al (2011), who worked with Organic, mineral and foliar fertilization in camu-camu plants (131 mg.kg -1 of Mn), but verified values are within those suitable for plant nutrition accordingly to Dechen & Nachtigall (2006), who consider an adequate concentrations between 20 and 500 mg.kg -1 . However, Mn levels linked to plant toxicity, are observed in plants established in lowland soils under flooding and an inadequate irrigation, since the availability of Mn 2+ is favored under these conditions (Dechen & Nachtigall, 2006).…”
Section: Micronutrient Contentscontrasting
confidence: 44%
See 4 more Smart Citations
“…The leaf contents of Mn, cited in this study are higher than those reported by Esashika et al (2011), who worked with Organic, mineral and foliar fertilization in camu-camu plants (131 mg.kg -1 of Mn), but verified values are within those suitable for plant nutrition accordingly to Dechen & Nachtigall (2006), who consider an adequate concentrations between 20 and 500 mg.kg -1 . However, Mn levels linked to plant toxicity, are observed in plants established in lowland soils under flooding and an inadequate irrigation, since the availability of Mn 2+ is favored under these conditions (Dechen & Nachtigall, 2006).…”
Section: Micronutrient Contentscontrasting
confidence: 44%
“…As a result, it has long been thought that these leaf content of K was higher than those reported by Viégas et al (2004), who showed levels between 5.2 a 6.0 g.kg -1 and also to those observed by Esashika et al (2011), who worked with mineral fertilizer (6.05 g.kg -1 of K). Nevertheless, the result of Ca is within those suitable for camu-camu plants, since the ideal range for foliar contents of this nutrient is from 7.1 g.kg -1 (Viégas et al, 2004) to 11.7 g.kg -1 (Esashika et al, 2011).…”
Section: Macronutrient Contentscontrasting
confidence: 38%
See 3 more Smart Citations